(untitled) (Journal of Architectural Design, 2022)
In design, architectural and design activities, business owners are required to have a highly developed geometric imagination. The role of engineering and computer graphics taught in higher education institutions in the formation and development of spatial imagination in future designers, architects and designers is special. This article presents a study material designed to use students’ spatial imagination in the development of the process of constructing imaginary point geometric sets by memorization